Decreased Antioxidant Capacity in Corn Farmers Occupationally Exposed to the Mixture of Herbicides - Unchisa Intayoung; Kanyapak Kohsuwan; Klintean Wunnapuk; Ratana Sapbamrer; Supakit Khacha-Ananda (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The application of herbicides has been a common practice in worldwide agriculture, mainlywith the goal to increase efficacy of weed control. So, most farmers faced a greater risk of herbicideexposure to develop adverse health effects from oxidative stress-induced herbicides. The aim of this studyis to determine the urinary total antioxidant capacity (TAC) and 8-isoprostane levels in farmers using themixture of herbicides in Long District, Phrae Province, Thailand.Methods: Ninety-three participants were recruited. The spot urine samples (pre- and post-work) werecollected. The urinary TAC was determined using ABTS radical scavenging assay. The urinary 8-isoprostanelevel was investigated by commercial ELISA kit.Results: Most farmers worked on a farm during 1-5 h/day. Fifty-five percents of participants used themixture of herbicide while working between glyphosate and paraquat as well as glyphosate and 2,4-D. Theurinary TAC levels in pre-work urine sample of farmers applied combining herbicides were significantlyhigher than that level in their post-work urine sample. However, there was no significant difference betweenpre- and post-work urinary 8-isoprostane in farmers applied combining herbicides.Conclusion: The results suggest that occupational exposure to mixture of glyphosate herbicides plus paraquator 2,4-D could induce abnormal oxidative stress value especially antioxidant defense among agriculturalworkers.